IMPLEMENTASI PENDEKATANLEAN SIX SIGMAUNTUK PENINGKATAN MUTU LULUSAN (STUDI PADA PPS. MMP UKSW SALATIGA) - Meylani Aljeinie Tijow; Supramono Supramono (Kelola: Jurnal Manajemen Pendidikan, 2015)
The main purpose of the implementation of Lean Six Sigma in this study is to improve the graduates’ quality of PPs. MMP UKSW. Although PPs. MMP UKSW has an A accreditation, there are some graduates that graduated through a long study period that exceed the ideal standart. The method that used is DMAIC methodology (Define, Measure, Analyze, Improvement, Control) with the quality indicator based on accreditation assessment of master degree. The data is collected by FGD (Focus Group Discussion) and analyzed by fishbone diagram and 5Whys. The result showed that beside the length of study period, the main problem of graduates’ quality of PPs. MMP UKSW is the lack of alumnis’ participation. The root problem of study period is focused on how the student are wasting the time to wait writing the proposal or thesis, while the root problems for alumnis’ participation is because of their busy job. Based on those findings, there are 7 strategies for institution to improve the quality of graduates.